The Influence Of Location, Product Variety, And Service Quality On Consumer Purchasing Decisions At Em Store Purbalingga - Nanda Zabrina Auberta; Arini Hidayah; Dian Widyaningtyas; Luthfi Zamakhsyari (UNIVED Press, 2026)
This study examines the influence of location, product variety, and service quality on consumer purchasing decisions at eM Store Purbalingga. Employing a quantitative research methodology, data were obtained through the distribution of questionnaires to 120 purposively selected respondents, based on the criteria of being at least 17 years old, residing in Purbalingga, and having previously made a purchase at eM Store. The sample size was determined using the Slovin formula from a population of 3,600 consumers (as of December 2024), with a margin of error of 10%. Multiple linear regression analysis revealed that all three variables have a positive and significant effect on purchasing decisions.